Fast-ion orbit sensitivity of neutron and gamma-ray diagnostics for one-step fusion reactions. (1st November 2022) - Järleblad, H.; Stagner, L.; Salewski, M.; Eriksson, J.; Nocente, M.; Rasmussen, J.; Štancar, Ž.; Kazakov, Ye.O.; Simmendefeldt, B.; JET Contributors,
Abstract: Fast ions in the MeV-range can be diagnosed by neutron emission spectroscopy (NES) and gamma-ray spectroscopy (GRS). In this work, we present orbit weight functions for one-step fusion reactions, using NES and GRS diagnostics on perpendicular and oblique lines-of-sight (LOS) at Joint European Torus (JET) as examples. The orbit weight functions allow us to express the sensitivities of the diagnostics in terms of fast-ion (FI) orbits and can be used to swiftly reproduce synthetic signals that have been computed by established codes. For diagnostically relevant neutron energies for the D(D, n) 3 He reaction, the orbit sensitivities of the NES diagnostics follow a predictable pattern. As the neutron energy of interest increases, the pattern shifts upwards in FI energy. For the GRS diagnostic and the T(p, γ ) 4 He reaction, the orbit sensitivity is shown to be qualitatively different for red-shifted, blue-shifted and nominal gamma birth energies. Finally, we demonstrate how orbit weight functions can be used to decompose diagnostic signals into the contributions from different orbit types. For a TRANSP simulation of the JET discharge (a three-ion ICRF scenario) considered in this work, the NES signals for both the perpendicular and oblique LOS are shown to originate mostly from co-passing orbits. In addition, a significant fraction of the NES signal for the oblique LOS is shown to originate from stagnation orbits.